Survey on Pre-Processing Web Log Files in Web Usage Mining - G Appa Rao, Rita Roy (International Journal of Advanced Science and Technology, 2020)
Web mining is to decide and extricate helpful data. In the web age web applications are expanding at gigantic speed and the web clients are expanding at exponential speed. As number of clients develops, site distributers are having expanding their data for pulling in and fulfilling clients. It is conceivable to follow the clients’ quintessence and collaborations with web applications through web server log record and Web log document contains just (.txt) record. The information put away in the web log record comprise of enormous measure of disintegrated, inadequate, and pointless data. In view of enormous measure of superfluous information’s accessible in the web log record, a unique log document can’t be straightforwardly utilized in the web use mining. So pre-processing method is connected to improve the quality and effectiveness of a web log record. Various procedures are connected in pre-processing that is information cleaning, information combination, information joining. In this paper we will overview distinctive pre-processing system to recognize the issues in web log document and to improve web utilization digging pre-processing for example mining and investigation.